2018
DOI: 10.1093/gigascience/giy101
|View full text |Cite
|
Sign up to set email alerts
|

The genome of the golden apple snail Pomacea canaliculata provides insight into stress tolerance and invasive adaptation

Abstract: BackgroundThe golden apple snail (Pomacea canaliculata) is a freshwater snail listed among the top 100 worst invasive species worldwide and a noted agricultural and quarantine pest that causes great economic losses. It is characterized by fast growth, strong stress tolerance, a high reproduction rate, and adaptation to a broad range of environments.ResultsHere, we used long-read sequencing to produce a 440-Mb high-quality, chromosome-level assembly of the P. canaliculata genome. In total, 50 Mb (11.4%) repeat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
105
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(117 citation statements)
references
References 80 publications
(72 reference statements)
7
105
0
Order By: Relevance
“…In this study, recent TE explosions were observed in all 4 invasive mollusks but were absent in the other noninvasive mollusks. Genes located near recently emerged TEs were enriched in the function of stress responses, which is consistent with our previous findings in the golden apple snail 39 , indicating that the recent TE explosion might be a common genetic force contributing to biological invasion. In addition, WGD has been proposed to provide robustness of genetic variation and redundant gene resources for the rapid evolution of novel functions, driving phenotypic complexity and ecological adaptation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, recent TE explosions were observed in all 4 invasive mollusks but were absent in the other noninvasive mollusks. Genes located near recently emerged TEs were enriched in the function of stress responses, which is consistent with our previous findings in the golden apple snail 39 , indicating that the recent TE explosion might be a common genetic force contributing to biological invasion. In addition, WGD has been proposed to provide robustness of genetic variation and redundant gene resources for the rapid evolution of novel functions, driving phenotypic complexity and ecological adaptation.…”
Section: Discussionsupporting
confidence: 91%
“…However, the available genomic resources for Mollusca are still quite insufficient in comparison with those for other large phyla such as Arthropoda and Nematoda 29, 30 . The genomes of aquatic mollusks such as California sea hare 31 , Pacific oyster 32 , pearl oyster 33, 34 , owl limpet 35 , California two-spot octopus 36 , golden mussel 37 , Biomphalaria glabrata 38 , and golden apple snail 39 have been sequenced, whereas few terrestrial species in Mollusca have well-documented genomic information. Recently, the genomic data of the invasive land snail A. fulica were released, but without in-depth studies of related biological issues 40 .…”
Section: Introductionmentioning
confidence: 99%
“…The featured domains include AIG1, coiled-coil, TMi (transmembrane domain from inside to outside of a membrane), TMo (transmembrane domain from outside to inside of a membrane), and other special functional domains: DD-CARD (death domain CARD type), DD-Fas (death domain Fas type), Hint (hint/hedgehog), armadillo (ARM)-type fold and Pkinase (protein kinase). c. Gene structures corresponding to representative transcripts of AIG genes were shown with exon, intron and untranslated region (UTR) in different colors Table 2 Summary of predicted numbers of AIG family members in B. glabrata and 9 molluscan species Phylogenetic relationships among B. glabrata and 9 additional molluscan species were inferred according to published literature [37][38][39] seemed to originate with B. pfeifferi sequences, but most contained terminal branches from both species, again emphasizing the overall similar representation of AIGs across the two species. At least five major clusters contained only B. pfeifferi sequences, and the overall number of terminal branches represented by B. pfeifferi was higher (142) than for B. glabrata (101).…”
Section: Aig Genes In 9 Additional Species Of Molluscamentioning
confidence: 99%
“…Indexed among the worst invasive species in the world, the freshwater snail Pomacea canaliculata has gained significant attention within the scientific community [1,2]. This is principally due to the different typologies of damages that the snail can cause to human economy and health.…”
Section: Introductionmentioning
confidence: 99%
“…With the idea of targeting the golden apple snail immune system as a tool to control its distribution, we sought to investigate the basic immune components in this snail. As all lophotrochozoa, P. canaliculata possesses an exclusively innate immune system [4], which, together with specific anatomical and physiological features [1], contributes to the snail's notorious adaptability. Morphological, ultrastructural, and flow cytometry studies converged towards the conclusion that the snail immune cellular component is principally represented by circulating hemocytes, divided into Group I and Group II hemocytes on the basis of their size.…”
Section: Introductionmentioning
confidence: 99%